Occupational sex segregation and management-level wages in Germany: What role does firm size play? - Anne Busch; Elke Holst (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The paper analyzes the gender pay gap in private-sector management positions based on German panel data and using fixed-effects models. It deals with the effect of occupational sex segregation on wages, and the extent to which wage penalties for managers in predominantly female occupations are moderated by firm size. Drawing on economic and organizational approaches and the devaluation of women's work, we find wage penalties for female occupations in management only in large firms. This indicates a pronounced devaluation of female occupations, which might be due to the longer existence, stronger formalization, or more established old-boy networks of large firms.
Keywords: B54; J16; J24; J31; J71; L2; M51; 330; Gender pay gap; managerial positions; occupational sex segregation; gendered organization; firm size